EKSPLORASI KAJIAN ETNOMATEMATIKA MELAYU PADA REPLIKA BANGUNAN ISTANA KERAJAAN INDRAGIRI DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Nadia Alpian; Muhammad Fendrik; Zetra Hainul Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore ethnomathematics in the Replica of the Indragiri Royal Palace. This study uses an ethnographic method which is a method of qualitative research. The subjects of this study were 5 people. In this study, the main instrument was the researcher himself and the supporting instruments were observation, documentation and interviews. Data analysis techniques were carried out by means of data reduction, data presentation and drawing conclusions. The results of this study indicate that there is a philosophical meaning of the Replica of the Indragiri Royal Palace Building, namely several building elements have their philosophical values, the tiered pyramid roof symbolizes the social hierarchy and the relationship between humans and God, wooden pillars symbolize strength and unity, wooden stairs reflect the levels of life, floral ornaments (bamboo shoots, flowers, leaves) symbolize fertility and growth, the symmetry of doors and windows symbolizes order and justice. There is ethnomathematics in the Indragiri Royal Palace Replica which includes counting or counting activities, calculating activities, measuring, determining locations,and designing. From this ethnomathematics activity, there are mathematical concepts in it which include the concept of counting, plans and cardinal directions, geometric concepts such as geometric shapes and flat shapes. With the ethnomathematics findings in the Indragiri Royal Palace Replica, it is closely related to mathematics learning in elementary schools which can be used as learning material or resources for students in elementary schools.